2010
DOI: 10.1111/j.1464-410x.2009.08846.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and normal ranges for the Patient’s Perception of Intensity of Urgency Scale in asymptomatic women

Abstract: Female Lower Urinary Tract Symptoms Long Form, to exclude those with bothersome lower urinary tract symptoms. Participants completed two separate 7-day bladder diaries with a 1-week interval between. Reliability was assessed using intraclass correlation, Spearman's correlation, and Student's t -test. RESULTSForty volunteers were recruited. Most (67.5%) reported no urgency episodes. Convenience voids accounted for 26.8% of all voids. There was a significant positive effect of age ( r = 0.34, P = 0.034) on urgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…Urgency was evaluated using the PPIUS which scored the intensity of urgency at each void with a 5 point scale [21]. Questionnaires were completed by the patients prior to clinical examination for baseline and follow-up assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Urgency was evaluated using the PPIUS which scored the intensity of urgency at each void with a 5 point scale [21]. Questionnaires were completed by the patients prior to clinical examination for baseline and follow-up assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Cartwright, Srikrishna, Cardazo, & Robinson [7] found that the PPIUS has good reliability, excellent known groups validity and convergent validity, and high responsiveness when used in a clinical trial study with adult women with OAB. The test-retest reliability of the PPIUS incorporated into a seven-week diary completed before and after a one-week interval has been reported in a group of asymptomatic women [8]. However, content validity has yet to be supported with qualitative research in patients with OAB.…”
Section: Introductionmentioning
confidence: 99%
“…The scores and current terms/descriptions are given, together with our suggested interpretations based on the ICS definition of urgency (shown italicised in square brackets) Patient perception of intensity of urgency scale (PPIUS): An assessment of the intensity of bladder sensation and urgency during completion of a bladder diary. The PPIUS has been validated in a study of 40 female volunteers, where it gave good test-retest reliability using a 7-day bladder diary, with the ability to discriminate between asymptomatic controls and previously reported values for patients with OAB[18] 0No urgency: 'I felt no need to empty my bladder but did so for other reasons [No desire to void] 1 Mild urgency: 'I could postpone voiding as long as necessary without fear of wetting myself' [First desire to void] 2 Moderate urgency: 'I could postpone voiding for a short while without fear of wetting myself' [Moderate or strong desire to void-or, possibly, successful inhibition of true urgency] 3 Severe urgency: 'I could not postpone voiding but had to rush to the toilet in order not to wet myself' [Urgency. Might be better described as 'I had urgency and could not postpone voiding but had to rush to the toilet in order not to wet myself'] 4 Urge incontinence: 'I leaked before arriving at the toilet' [Urgency incontinence.…”
mentioning
confidence: 99%